2012
DOI: 10.1186/1752-0509-6-70
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of calcium signaling and membrane electrophysiology in cerebellar Purkinje neurons associated with ataxia

Abstract: BackgroundMutations in the smooth endoplasmic reticulum (sER) calcium channel Inositol Trisphosphate Receptor type 1 (IP3R1) in humans with the motor function coordination disorders Spinocerebellar Ataxia Types 15 and 16 (SCA15/16) and in a corresponding mouse model, the IP3R1delta18/delta18 mice, lead to reduced IP3R1 levels. We posit that increasing IP3R1 sensitivity to IP3 in ataxias with reduced IP3R1 could restore normal calcium response. On the other hand, in mouse models of the human polyglutamine (poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 101 publications
(221 reference statements)
1
34
0
Order By: Relevance
“…Similar to the homozygous opt mice, the in-frame deletion of residues 1533-1538 in the middle coupling domain of D18 mutants resulted in significant reduction of IP 3 R1 expression in cerebellar PCs [54]. The D18 mutant mice may be used as a valuable mouse model for SCA15/16 [55].…”
Section: Mutations In the Ip3r1 Gene And Ataxiasmentioning
confidence: 89%
“…Similar to the homozygous opt mice, the in-frame deletion of residues 1533-1538 in the middle coupling domain of D18 mutants resulted in significant reduction of IP 3 R1 expression in cerebellar PCs [54]. The D18 mutant mice may be used as a valuable mouse model for SCA15/16 [55].…”
Section: Mutations In the Ip3r1 Gene And Ataxiasmentioning
confidence: 89%
“…Inspired by the hypothesis above, it was proposed that mutant Ataxin‐1 might also cause excessive IP 3 ‐mediated dendritic Ca 2+ release from ER stores in SCA1 pathology. In addition, a recent computational study in a model of SCA1 proposed that assumed supersensitivity of IP 3 receptors could lead to upregulation of Ca 2+ signalling including mGluR‐mediated IP 3 ‐induced Ca 2+ release, regardless of reduced expression of IP 3 receptor 1, SERCA and mGluR (Brown & Loew, ). However, we think that these proposals are unlikely in SCA1 pathology, because Ataxin‐1 is localized to the PC nucleus (Skinner et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our proteomic screen also revealed that a significant number of mitochondrial proteins involved in the ETC complexes and the ATP synthase were downregulated in mutant PCs, thereby affecting bioenergetics and proper mitochondrial functioning. Additionally, it is well accepted that calcium signaling is impaired in SCA1, SCA2 and SCA3 (Brown and Loew, 2012;Halbach et al, 2016;Kasumu et al, 2012;Pellistri et al, 2013) and as mitochondria are the second most important calcium storage organelle, improper mitochondrial functioning can negatively impact calcium homeostasis and neuronal transmission (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%